Attitudes, Beliefs and knowledge of teecherz furniture male workers towards voluntary consoling and testing for HIV infection - Makomeke, Chipochedenga; Nyamakura, Rudo; Chitura, Miriam; Makomeke, Patience Chido (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
Scaling up Voluntary Counseling and Testing (VCT) and treatment is a key priority in our global response to the epidemic. In the context of a growing number of strategies designed to achieve this treatment optimization, there is an urgent need for alternate delivery systems to increase access to and utilization of HIV counseling and testing facilities, the first point in the treatment cascade. Data, from the local industrial area Teecherz Furniture in Granite side, Harare, Zimbabwe supports an emerging body of literature that suggests that mobile VCT approaches, embedded in community contexts, are capable of reaching target groups thus far missed through the predominant health facility-based HIV testing approaches that currently exist. Roy’s adaptation model guided this study. The purpose of this study was to determine the attitudes, beliefs and knowledge of Teecherz Furnishers male workers towards voluntary counseling and testing for HIV. A descriptive study design was used. A simple random sampling of 30 participants was used. Data was collected using face to face interviews guided by a questionnaire. In terms of attitudes, 13 (43.3%) participants showed positive attitudes towards VCT by stating that they would make future decisions about their sexuality. Nineteen (63.3%) believed that VCT was leading to an increase in divorce rates. In terms of knowledge, 19 (63.3%) did not know what VCT is. The respondents of this study showed that they have the knowledge on both disease and the VCT HIV programme but mainly feared the issue of stigma and discrimination. The study therefore brought out the fact that knowledge does not necessarily influence attitude but there are several factors like family and friends support that may hinder one from making the decision. Based on these results, it is strongly recommended that Teecherz furnishers should continue mobilizing employees to go for VCT.